Pengaruh media ular tangga terhadap kemampuan berhitung siswa kelas 2 B SD Islam Surya Buana - Krisdamyanti, Erlysa (Maliki Interdisciplinary Journal, 2024)
The purpose of this study is to ascertain how the media series Snakes and Ladders has improved the numeracy abilities of Surya Buana Islamic Elementary School’s class II pupils. It is a qualitative descriptive research design. Twenty-one Surya Buana Islamic Elementary School class II B children served as the research subjects. With a percentage of 29% of the Pre-test score and 86% of the Post-test score, the research’s findings demonstrate that the media for the snake and ladder game has satiated the necessary requirements. Learning completeness, which at first only achieved 29% but increased to 77% after another test, is another metric that supports this requirement. According to the Pre-test and Post-test activity observation sheet, it